Answer:
4.4 miles
Step-by-step explanation:
c= sqrt 6^2+10^2
sqrt 36+100
Sqrt 136=11.66190378
10+6=16
16-11.66190378=4.33809622
The answer for this question is to treat people the way you want to be treated if you want the answer click the link below
Answer:
See below. <u><em>I assume that (x) = 8x2 - 7x + 3 is really (x) = 8x^2 - 7x + 3</em></u>
Step-by-step explanation:
Substitute the value of x given in f(x) into the equation f(x) = 8x^2 - 7x + 3
For example, f(0) would be f(0) = 8(0)^2 - 7(0) + 3. f(0) = 3
f(-2) would be f(-2) = 8(-2)^2 - 7(-2) + 3.
= 8*4 + 14 +3
= 32 + 17 therefore f(-2) = 49
<u>x</u> <u>f(x)</u>
-2 49
-1 18
0 3
1 4
2 21
So if an equation was f(x)=x+4
you would automatically change f(x) into y
so it would y-y=x(x-x)
so you plug in the x and 4 which is the first y and x
y-4=x(x-x)
you switch the numbers around
so your final answer would be x-4
Answer:
3/4
Step-by-step explanation:
In the above equation the y-intercept is -1 and the slope of the equation is 3/4